Sistemas de informação para a alta administração das empresas: estudo de caso em uma instituição financeira - Helena Alaide Mortimer Macedo (2000)
Information systems in most organizations are not efficient to provide sufficient information to their executives in order to support strategic or even routine decisions. This issue motivated this research, which main objective was to identify key elements in the implementation of information systems for high administration executives. A literature review was developed with focus on the decision-making process and business intelligence, as well as on their relationship with information for management. The research also included information systems for high management levels in organizations. A case study in a financial institution Banco Mercantil do Brasil was performed. The development of executive information systems and the availability of management information in a business enterprise is discussed and presented. The approach developed for the case study consisted of four phases: selection of the institution; development of interview forms and strategy; interviews; compilation and analysis of the results. The research was successful, since many literature review conclusions were verified in the real business environment. One of the main difficulties in the implementation of executive information systems was also evident: the development of a well-structured database, which allows the distribution of executive information suitable for the professionals and their context. This task demands the knowledge of management information needs, a sharp view of the business, high investments in information technology, and technical expertise of the systems development team.